The Impact of Artificial Intelligence on Online Shopping - Gantumur, Khuslen (European Scientific Journal, ESJ, 2025)
This research examines how artificial intelligence (AI) influences consumer purchase intentions in online shopping. Reviewing previous related studies examines how AI tools like chatbots, personalized recommendations, and user identification systems shape consumer behavior and decision-making. The findings show that AI enhances customer experiences by tailoring shopping journeys, increasing engagement, and simplifying decision-making. The study also points out a lack of research on the ethical side of AI marketing, including concerns about data privacy, cybersecurity, and consumer trust. These issues are becoming increasingly important as AI systems handle more sensitive data. Businesses are encouraged to focus on transparency and ethical practices to build consumer trust while using AI to improve marketing strategies and customer satisfaction. The research provides valuable insights for companies, showing how AI investments can give them a competitive edge by creating more personalized and efficient shopping experiences.